2017
DOI: 10.1007/s12275-017-7088-x
|View full text |Cite
|
Sign up to set email alerts
|

Coptidis Rhizoma extract inhibits replication of respiratory syncytial virus in vitro and in vivo by inducing antiviral state

Abstract: Coptidis Rhizoma is derived from the dried rhizome of Ranunculaceous plants and is a commonly used traditional Chinese medicine. Although Coptidis Rhizoma is commonly used for its many therapeutic effects, antiviral activity against respiratory syncytial virus (RSV) has not been reported in detail. In this study, we evaluated the antiviral activities of Coptidis Rhizoma extract (CRE) against RSV in human respiratory tract cell line (HEp2) and BALB/c mice. An effective dose of CRE significantly reduces the repl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…Magnoflorine and tinosporide isolated from T. cordifolia inhibits the HIV-1 protease active site with a very high affinity [71]. Palmatine inhibits respiratory syncytial virus in vitro and in vivo by inducing an antiviral state [72]. Furthermore, using the molecular docking approach, we and others have demonstrated the possible use of W. somnifera against SARS-CoV-2, wherein withanone, bound at the interface of the ACE2-RBD complex, and interrupted the electrostatic interactions between the RBD and ACE2.…”
Section: Discussionmentioning
confidence: 99%
“…Magnoflorine and tinosporide isolated from T. cordifolia inhibits the HIV-1 protease active site with a very high affinity [71]. Palmatine inhibits respiratory syncytial virus in vitro and in vivo by inducing an antiviral state [72]. Furthermore, using the molecular docking approach, we and others have demonstrated the possible use of W. somnifera against SARS-CoV-2, wherein withanone, bound at the interface of the ACE2-RBD complex, and interrupted the electrostatic interactions between the RBD and ACE2.…”
Section: Discussionmentioning
confidence: 99%
“…Upon virus infection, host cells rapidly mount type I IFN responses. Pattern recognition receptors (PRRs) play an important role at the early stage of infection [3,13,[35][36][37][38][39][40][41][42]: MDA5, RIG-I, and toll-like receptors (TLR). MDA5 and RIG-I are known to sense the RNA genome of the invading pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…PLT at a dose of 55 μM inhibited viral replication and decreased the death rate of infected HEp2 cells by almost 75% compared with the control group. Additionally, a significant increase in the level of IL‐6 and IFN‐β in HEp2 cells was observed, which indicated that the alkaloid had immunomodulatory properties (Lee et al, ).…”
Section: Pharmacology Of Pltmentioning
confidence: 98%